PLENARY: Managing Non-COVID Cases in Times of COVID - Abdul Hamid, Farique Rizal (International Journal of Human and Health Sciences (IJHHS), 2022)
The global context towards sustainable development has essentially changed with the COVID- 19 pandemic. The world faces the greatest social, economic and environmental challenges. This pandemic is characterized by its rapid spread, differential recovery rate and susceptibility to elderlies and people with weak immune systems. The impact of COVID-19 lockdown can distract the management plan and exacerbate the prognosis of non-COVID-19 patients. There are many lessons the world can learn from this disastrous pandemic outbreak for us to revise and strategize an efficient disaster management system which includes non-COVID-19 cases. The survival of non-COVID-19 cases is still a mystery as the pandemic waves are always uncertain. The key to unlocking the secret is the balancing-resilience strategy in the new normal disaster management framework. This pandemic offers an opportunity to make the world resilient to multiple hazards while sustaining the best care for non-COVID-19 patients. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S5